Membranous location of EGFR immunostaining is associated with good prognosis in renal cell carcinoma - Kallio, J P (Nature Publishing Group, 2003)
Epidermal growth factor receptor (EGFR) is a key factor in tumorigenesis. The association between EGFR expression and prognosis in renal cell carcinoma (RCC) is not clear. In our study of 134 RCCs, the cellular location of immunostaining was evaluated and patients with EGFR-positive tumours with prominent membranous staining had a good prognosis. Their overall survival was significantly longer (P=0.004) than that of patients with either EGFR-negative tumours or with mainly cytoplasmic staining. However, further studies on the different EGFR expression patterns in RCC are needed to clarify their role in the progression of the disease.